The Effect of Financial Performance Measured With Rentability Ratio Against Dividend Payout Ratio (Empirical Study on Manufacturing Companies Group Listed on BEI) - Imas Della Fauzi; Rukmini Rukmini (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2018)
This study aims to examine whether there is a significant effect of the company's financial performance as measured by the ratio of profitability with Return on Assets (ROA), Return On Equity (ROE), Return On Investment (ROI) and Net Profit Margin (NPM) to Dividend Payout Ratio (DPR). The data collected is obtained from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange period 2013-2015. The analysis used to know how big the influence of ROA, ROE, ROI NPM to DPR company, writer do statistical analysis done by using descriptive analysis, doubled linear regression, correlation coefficient and coefficient of determination. While testing the hypothesis using F test for simultaneous test and t test partially, using SPSS 16. Based on the results of data processing, obtained regression equation Y = 31.225 + 1.209 X₁ - 0.106 X₂ + 0.505 X₃ - 0.708 X₄ + ε, analysis results Statistics simultaneously obtained the value of determination coefficient of 28.3%. While the rest equal to 71.7% influenced by other factors. Based on hypothesis test by using significant level α = 0,05 result of F test, show that together regression model can be used to explain the relation between Return on Asset, Return On Equity, Return On Investment and Net Profit Margin to Dividend Payout Ratio. Keywords: Return on Assets, Return on Equity, Return On Investment and Net Profit Margin, Dividend Payout Ratio